Ethical Issues in Decision-making Regarding the Elderly Affected by Coronavirus Disease 2019: An Expert Opinion - David Martínez-Sellés (Radcliffe Medical Media, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is resulting in ethical decisions regarding resource allocation. Prioritisation reflects established practices that regulate the distribution of finite resources when demand exceeds supply. However, discrimination based on sex, race or age has no role in prioritisation unless clearly justified. The risk posed by COVID-19 is higher for elderly people than for younger people, so older adults should be prioritised in preventive measures. In the case of people who already have COVID-19, healthcare professionals might prioritise those most likely to survive. Making decisions based on chronological age alone is not justified; in addition to age, other aspects that determine theoretical life expectancy must be taken into account. Individualised correct prioritisation in the allocation of scarce resources is essential to good clinical practice.